2013
DOI: 10.1002/chem.201300262
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Nanoparticles Confined in Graphene Films and Their Electrochemical Properties

Abstract: The development of novel nanostructured electrode materials with high performance and based on abundant elements is a key element in the societal pursuit of sustainable energy. Graphene-based structures with rich macroporosity and high conductive networks are promising components to develop novel electrode materials. Herein, we described a facile procedure to confine Ni(OH)2 particles in a graphene film, leading to a new sandwich-like hybrid structure. The hybrid film offers simultaneously ordered ion diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Various "spacers" such as metal oxides, conductive polymers, and carbon materials were chosen to incorporate into the interlayers of graphene. [26][27][28] However, most of the non-carbon "spacers" improve the electrochemical properties by increasing the pseudo-capacitance, which is not helpful for the improvement of CDI capacity. Besides, the carbon "spacers" such as activated carbon and mesoporous carbon are usually clumpy and massive, which cannot be well distributed in the graphene sheets and thus it is hard to ensure the effective exfoliation of graphene sheets within the whole composite structure.…”
Section: Introductionmentioning
confidence: 99%
“…Various "spacers" such as metal oxides, conductive polymers, and carbon materials were chosen to incorporate into the interlayers of graphene. [26][27][28] However, most of the non-carbon "spacers" improve the electrochemical properties by increasing the pseudo-capacitance, which is not helpful for the improvement of CDI capacity. Besides, the carbon "spacers" such as activated carbon and mesoporous carbon are usually clumpy and massive, which cannot be well distributed in the graphene sheets and thus it is hard to ensure the effective exfoliation of graphene sheets within the whole composite structure.…”
Section: Introductionmentioning
confidence: 99%
“…17 Davies et al used a pulsed electrodeposition technique to create flexible, and uniform graphene/polypyrrole hybrid films that exhibit a high energy density of around 33 Wh kg -1 . 18 Moreover, the incorporation of certain inorganic substances, such as nanoparticles of manganese oxides, [19][20][21] iron oxide, 22 tin oxide 23 or Ni-based oxides/hydroxides [24][25][26][27] confined within the graphene films has likewise attracted widespread attention. Thus, Gao et al reported the design of solid-state asymmetric supercapacitors based on free-standing carbon nanotube/graphene and Mn 3 O 4 nanoparticles/graphene films.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, low efficiency, high cost, and poor oxide/C interfacial interaction are inevitable. [7,18] In addition, the intrinsic shortages of carbonaceous materials and metal oxides/hydroxides always result in compromised electrochemical performances: Large capacitances are acquired at the expense of poor cycle lifetimes, [19,20] or vice versa. [11,12] Recently, the introduction of electron-donating nitrogen heteroatoms to carbon materials has been proposed to achieve superior performances, [21][22][23][24] yet expensive resources and timeconsuming carbonization are often used to fabricate N-doped carbon materials.…”
Section: Introductionmentioning
confidence: 99%